BRAT1 gene compound heterozygous mutations causing lethal neonatal rigidity and multifocal seizure syndrome: a case report - Qin, Dong-Yuan; Tang, Qin-Qin; Feng, Dan; Song, Yan-Jun; Cheng, Zi-Huan; Ma, Rui-Cong; Sun, Ke; Wang, Fan (Frontiers in Pediatrics, 2026)
BackgroundBiallelic BRCA1-associated ataxia telangiectasia mutated activator 1 (BRAT1) gene mutations can result in lethal neonatal rigidity and multifocal seizure syndrome (RMFSL), characterized by refractory epilepsy, hypertonia, autonomic dysfunction, and early death. This study reports an infant with RMFSL bearing novel compound heterozygous BRAT1 gene mutations, including a rare pathogenic synonymous variant.Case presentationA male infant born at 37 weeks of gestation presented with seizures shortly after birth. Clinical features included refractory epilepsy, bilateral clubfoot deformity, and respiratory failure. Whole-exome sequencing identified compound heterozygous BRAT1 gene mutations (c.1395G>C, p.Thr465Thr and c.1297delC, p.Leu433Trpfs*). The c.1395G>C variant is a synonymous mutation with a predicted high-risk impact on mRNA splicing, whereas c.1297delC is a previously unreported novel frameshift mutation. These variants were inherited from phenotypically normal, healthy parents.Despite the provided care, the infant died at one month of age.ConclusionThis case highlights that synonymous BRAT1 variants affecting mRNA splicing can be pathogenic, leading to severe RMFSL. The findings expand the genotypic spectrum and underscore the need for comprehensive bioinformatics analysis of non-coding consequences in genetic testing.